Deer, wolves, and people: costs, benefits and challenges of living together - Martin, Jean‐Louis; Chamaillé‐Jammes, Simon; Waller, Donald M. (Biological reviews of the Cambridge Philosophical Society, 2020)
ABSTRACT Human‐driven species annihilations loom as a major crisis. However the recovery of deer and wolf populations in many parts of the northern hemisphere has resulted in conflicts and controversies rather than in relief. Both species interact in complex ways with their environment, each other, and humans. We review these interactions in the context of the ecological and human costs and benefits associated with these species. We integrate scattered information to widen our perspective on the nature and perception of these costs and benefits and how they link to each other and ongoing controversies regarding how we manage deer and wolf populations. After revisiting the ecological roles deer and wolves play in contemporary ecosystems, we explore how they interact, directly and indirectly, with human groups including farmers, foresters, shepherds, and hunters. Interactions with deer and wolves generate various axes of tension, posing both ecological and sociological challenges. Resolving these tensions and conflicts requires that we address key questions using integrative approaches: what are the ecological consequences of deer and wolf recovery? How do they influence each other? What are the social and socio‐ecological consequences of large deer populations and wolf presence? Finally, what key obstacles must be overcome to allow deer, wolves and people to coexist? Reviewing contemporary ecological and sociological results suggests insights and ways to improve our understanding and resolve long‐standing challenges to coexistence. We should begin by agreeing to enhance aggregate benefits while minimizing the collective costs we incur by interacting with deer and wolves. We should also view these species, and ourselves, as parts of integrated ecosystems subject to long‐term dynamics. If co‐existence is our goal, we need deer and wolves to persevere in ways that are compatible with human interests. Our human interests, however, should be inclusive and fairly value all the costs and benefits deer and wolves entail including their intrinsic value. Shifts in human attitudes and cultural learning that are already occurring will reshape our ecological interactions with deer and wolves.